STRATEGY AND TYPE OF RELATIVE CLAUSE IN KLATEN JAVANESE - Maharsi Sri Wigati; Rawuh Yuda Yuwana (PT Akselerasi Karya Mandiri, 2023)
Relative clauses are essential for updating specific nouns or pronouns that can be used as explanatory meanings. This research is to study the use of markers